PENINGKATAN HASIL BELAJAR SISWA DIKARENAKAN KOMPETENSI GURU - Soedjanarto, ; M. Yudy Firdaus, (Pendidikan Ekonomi, 2009)
Teachers competence is a significant factor in enhancing the quality of education in the way the teachers way of teaching affects the students learning achievement. This study , therefore, intended to find out the extent to which the economics teacher influenced the students achievement. On the base of the value of determinant coefficient, it indicated the influence of 50 % between independent variable and dependent variable, and another 50 % was influenced by other variables( other than variables X1 and X2). The result of F test showed that the influence of independent and dependant varibles were significant. Thus, it can be concluded that the influence of the economics teachers competence to the  achievement of the eleventh graders at SMA Negeri 2 Bojonegoro was significant.